Evaluation of wetting, structural and thermal properties of electrospun nanofibers at different pineapple leaf fiber / polyethylene terephthalate ratios - Muyassarah Abdul Aziz, Fatimah; Norasmah Surip, Siti; Ahmad Sekak, Khairunnadim; Khairun Anwar Uyup, Mohd; Ahmad Tarawneh, Mou'ad; Hua Lee, Seng (Maderas. Ciencia y Tecnología, 2021)
In this study, pineapple leaf fiber and polyethylene terephthalate electrospun nanofibers were produced via electrospinning process. Six ratios of pineapple leaf fiber/polyethylene terephthalate, namely 1/10; 1/7,5; 1/5; 1/1 and 1,3/1 were prepared and their wetting, structural and thermal properties were characterised. Wetting properties of this sample were studied using contact angle measurement. X-Ray Diffraction, differential scanning calorimetry and thermogravimetric analysis were conducted to get better understanding on the structural and its thermal properties respectively. The results revealed that increasing the pineapple leaf fiber content simultaneously increased the ability of nanofibers to adsorb water as shown by lower contact angle degree with 81,6° and adsorption time of 15 seconds. An increase in pineapple leaf fiber ratio did not change the peak position in X-Ray Diffraction and no new peaks observed for any sample. However, the peak at 23° for samples with ratio 1/1 and ratio 1,3/1 exhibited higher intensity compared to that of pure polyethylene terephthalate. Thermal properties obtained from thermogravimetric analysis results suggested that thermal properties were not influenced by the pineapple leaf fiber ratio. Overall, pineapple leaf fiber/polyethylene terephthalate electrospun nanofibers produced at the ratio of 1/1 displayed the optimum performance.